Sustainable weed management – What is it and how are we doing?. (10th December 2022) - McCauley, Cara; Legleiter, Travis; Herman, Rod; Rasoulpour, Reza; Schroeder, Jill; Pilcher, Todd; Meinders, Karen; Wright, Terry
Abstract: The topic of sustainability is popular in mainstream media and a common discussion theme, particularly for the agriculture discipline that serves the entire world. Individuals and corporations often have a desire to be sustainable in their practices, but the commentary on "being sustainable" can be confusing in terms of realistic practices. To define whether weed science is sustainable one must first identify the resource or object to be sustained. From a historical perspective, weed control in the United States over the past 40 yr has revolved around no-tillage row crop acres. The implementation of no-till or reduced till has undeniable benefits in sustaining natural resources, especially two of our most valuable resources: soil and water. While the overall trend toward chemical weed control has been shown to decrease agriculture's impact on the environment, depending solely on herbicides is not sustainable long term with the rise in herbicide-resistant weed species. We also consider the benefits and challenges associated with agronomic trends within the context of sustainability and expand consideration to include emerging technology aligned to human health and environmental stewardship. The key to improving farming is producing more and safer food, feed, and fiber on less land while reducing adverse environmental effects, and this must be accomplished with the backdrop of human population growth and the desire for an improved standard of living globally. Emerging technologies provide new starting points for sustainable weed management solutions, and the weed science community can initiate the conversation on sustainable practices and share advancements with our colleagues and community members. In addition to broadening the sustainability concept, targeted and relevant communication tools will support the weed science community to have successful and impactful discussions.